THE INFLUENCE OF LEARNING FACILITIES AND FAMILY ENVIRONMENT ON STUDENTS' LEARNING MOTIVATION AT SMK NEGERI 10 JAKARTA - Maulidiya, Ayu; Marsofiyati; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
this study aims to determine the effect of learning facilities and family environment on student motivation at SMKN 10 Jakarta. This research was conducted for 7 months starting from December 2021 to July 2022. The method used in this study was a survey method. The respondent selection technique used Proportional Random Sampling in order to obtain a sample of 129 students from SMK Negeri 10 Jakarta. Data was collected through distributing questionnaires using a Likert scale. Based on the results of the research conducted, it was found that Learning Facilities had a positive and significant effect on students' learning motivation. The family environment has a positive and significant effect on students' learning motivation. Learning Facilities and Family Environment together have a positive and significant effect on students ' learning motivation .